eDNA metabarcoding survey reveals fine‐scale coral reef community variation across a remote, tropical island ecosystem - West, Katrina M.; Stat, Michael; Harvey, Euan S.; Skepper, Craig L.; DiBattista, Joseph D.; Richards, Zoe T.; Travers, Michael J.; Newman, Stephen J.; Bunce, Michael (Molecular ecology, 2020)
Environmental DNA (eDNA) metabarcoding, a technique for retrieving multispecies DNA from environmental samples, can detect a diverse array of marine species from filtered seawater samples. There is a growing potential to integrate eDNA alongside existing monitoring methods in order to establish or improve the assessment of species diversity. Remote island reefs are increasingly vulnerable to climate‐related threats and as such there is a pressing need for cost‐effective whole‐ecosystem surveying to baseline biodiversity, study assemblage changes and ultimately develop sustainable management plans. We investigated the utility of eDNA metabarcoding as a high‐resolution, multitrophic biomonitoring tool at the Cocos (Keeling) Islands, Australia (CKI)—a remote tropical coral reef atoll situated within the eastern Indian Ocean. Metabarcoding assays targeting the mitochondrial 16S rRNA and CO1 genes, as well as the 18S rRNA nuclear gene, were applied to 252 surface seawater samples collected from 42 sites within a 140 km2 area. Our assays successfully detected a wide range of bony fish and elasmobranchs (244 taxa), crustaceans (88), molluscs (37) and echinoderms (7). Assemblage composition varied significantly between sites, reflecting habitat partitioning across the island ecosystem and demonstrating the localisation of eDNA signals, despite extensive tidal and oceanic movements. In addition, we document putative new occurrence records for 46 taxa and compare the efficiency of our eDNA approach to visual survey techniques at CKI. Our study demonstrates the utility of a multimarker metabarcoding approach in capturing multitrophic biodiversity across an entire coral reef atoll and sets an important baseline for ongoing monitoring and management.